Reconstructing Grammar Exercises: A Systemic Functional Grammar Approach - Fauzi, Ashar; Putra, Kristian Adi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
Despite the sufficient amount of language textbook analysis studies that have been conducted, little attention focused on grammar exercises analysis presented in the Indonesian junior high school English textbooks that facilitated the students to make meaning where functional grammar principles were adopted. This current study nuanced education artifacts analysis. The researchers intended to reveal to what extent the English grammar exercises present functional grammar exercises. Moreover, The study provided a practical suggestion to teachers, textbook developers, and language practitioners to revise and include the functional grammar approach in designing English grammar exercises. Anchored into critical document study, this study focused to find the representation of functional grammar exercises portrayed in an English language textbook where the mandated English language curriculum endorses genre-based and text-based language pedagogy in an Indonesian secondary school context. Two analytical tools were combined (i.e. transitivity analysis and critical discourse study) to reveal the existing English grammar exercises. The findings present a total of 88 English grammar exercises found in the textbook. However, 28 English grammar exercises indicated activities for the student to make meaning. The result provided a critical suggestion for grammar exercises revision that facilitates students to make meaning and understanding the social practices of the language. However, this study only provided a textbook analysis, further studies possibly focus on action studies where the functional grammar exercises were implemented in classroom activities.